Penyelesaian Sengketa Perbankan di Indonesia: Analisis Mekanisme Pengaduan Internal, Mediasi LAPSPI, dan Litigasi dalam Perspektif Perlindungan Konsumen - Rafael Ahmad Eryasafli; Siti Maharani; Muhammad Faiz Zakwan (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the effectiveness of dispute resolution mechanisms in Indonesia’s banking sector through three primary channels: internal complaint handling within banks, mediation facilitated by the Indonesian Alternative Dispute Resolution Institution for Banking (LAPSPI), and litigation. Using a normative juridical approach and qualitative analysis of legal frameworks, OJK regulations, academic literature, and relevant case studies, this research highlights the role of multi-layered dispute resolution in ensuring consumer protection, promoting access to justice, and maintaining financial system stability. The findings show that internal complaint mechanisms serve as a preventive legal tool, mediation offers a restorative and efficient alternative, while litigation remains the last resort due to its complexity, cost, and reputational risks. Challenges persist, particularly in public awareness, mediator capacity, and institutional readiness. This study underscores the need for stronger institutional cooperation, digitalization of dispute resolution systems, and enhanced compliance culture to achieve an effective, transparent, and equitable banking dispute resolution framework in Indonesia.